Ginseng and Ganoderma lucidum Use after Breast Cancer Diagnosis and Quality of Life: A Report from the Shanghai Breast Cancer Survival Study - Bao, Ping-Ping (Public Library of Science, 2012)
OBJECTIVE: To evaluate associations between quality of life (QOL) and use of ginseng and Ganoderma lucidum (G. lucidum) among breast cancer survivors. METHODS: Included in this study were 4,149 women with breast cancer who participated in the Shanghai Breast Cancer Survival Study. Ginseng use was assessed at 6-, 18-, and 36-month post-diagnosis surveys; G. lucidum use was assessed at the 6- and 36-month surveys. QOL was evaluated at the 6- and 36-month surveys. Multiple linear regression models were used to examine associations between ginseng and G.lucidum use and QOL assessed at the 36-month survey, with adjustment for potential confounders and baseline QOL. RESULTS: At 6 months post-diagnosis, 14.2% of participants reported regular use of ginseng and 58.8% reported use of G. lucidum. We found no significant associations between ginseng use at 6, 18, and 36 months post-diagnosis and participants’ total QOL score or individual scores for psychological, physical, or social well-being. Post-diagnosis G. lucidum use was positively associated with social well-being (adjusted mean difference: 1.26; 95% CI: 0.66, 1.86), but was inversely associated with physical well-being (adjusted mean difference: −1.16; 95% CI: −1.86, −0.47) with a dose-response pattern observed for cumulative number of times of use (P for trend <0.001 for both). CONCLUSION: We found no evidence that post-diagnosis ginseng use improved the QOL of breast cancer survivors. Post-diagnosis G. lucidum use was associated with better social well-being scores, but poorer physical well-being scores.